The Role of Interventional Radiology in the Pretransplant Management of Hepatocellular Carcinoma and Portal Vein Thrombosis - Shmelev, Karen; Thornburg, Bartley (Digestive Disease Interventions, 2019)
Hepatocellular carcinoma (HCC) is the most common primary liver tumor and is currently the leading indication for liver transplantation in the United States. Liver transplantation may provide a curative option for patients with HCC, but some present outside of the transplant criteria. Additionally, as the criteria for liver transplant eligibility in HCC are expanded and the incidence of disease increases, waitlist times are becoming progressively longer, which increases the chance of a patient suffering from disease progression while awaiting an organ becoming ineligible for transplant. Multiple studies have demonstrated the successful use of locoregional therapies, including trans-arterial chemoembolization and trans-arterial radioembolization, in downstaging HCC to within transplant criteria, as well as in preventing progression of disease in patients already listed for transplant. Cirrhotic patients also commonly develop portal vein thrombosis (PVT), which is a contraindication to transplantation at many centers. PVT can lead to worsened outcomes after transplant depending on the type of portal venous reconstruction that is performed. The purpose of this article is to discuss the integral role of interventional radiology in the care of these patients, including the role of transarterial therapies in the pretransplant treatment of HCC and the use of endovascular techniques to recanalize thrombosed portal veins in order to establish or maintain transplant eligibility.
Keywords: bridging hepatocellular carcinoma; downstaging hepatocellular carcinoma; portal vein recanalization; liver transplantation